2021
DOI: 10.3389/fendo.2021.726172
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Effect of Weekly Long-Acting Growth Hormone Replacement Therapy Compared to Daily Growth Hormone on Children With Short Stature: A Meta-Analysis

Abstract: BackgroundWe performed a meta-analysis to evaluate the efficacy and safety of weekly long-acting growth hormone replacement therapy compared to daily growth hormone in children with short stature.MethodsA systematic literature search up to April 2021 was performed and 11 studies included 1,232 children with short stature treated with growth hormone replacement therapy at the start of the study; 737 of them were using weekly long-acting growth hormone replacement therapy and 495 were using daily growth hormone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…This nding contradicts with Liyan Ma et al (32), which reported no signi cant difference in HV between daily GH and long-acting GH replacement treatment.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…This nding contradicts with Liyan Ma et al (32), which reported no signi cant difference in HV between daily GH and long-acting GH replacement treatment.…”
Section: Discussioncontrasting
confidence: 69%
“…In our meta-analysis, the weekly GH group had a slightly higher incidence of adverse events than the daily GH group (OR = 1.38, 95% CI 0.58 to 3.28; P = 0.47), albeit this difference was statistically insigni cant. In contrast, Liyan Ma et al (32) found no signi cant difference in the incidence of adverse events between long-acting growth hormone replacement treatment and daily growth hormone in children with short height in their meta-analysis. This is consistent with our ndings, which show that both treatment methods have identical safety pro les.…”
Section: Discussionmentioning
confidence: 82%
“…But for all practical purposes the current agreed GH cut off in the United States remains to be 10 ng/dL ( 32 ). The current published literature on long-acting GH research is also based on the GHD cut off of 10 ng/dl ( 13 , 14 ). In our patient cohort 36% had a peak ≤ 7 ng/dL on repeat GST; had we waited extended periods, perhaps they may have had lower GH peak levels.…”
Section: Discussionmentioning
confidence: 99%
“…A peak growth hormone (GH) level below 10 µg/dL is largely still clinically considered the cut-off for the diagnosis of GHD (9)(10)(11) in the United States and in other countries across the globe (12). Recent multi center international clinical studies regarding long-acting GH also all utilized 10mcg/dl as the GHD cut off (13,14).…”
Section: Introductionmentioning
confidence: 99%